Detection of "11-Nor-9-carboxy-Δ9 -Tetrahydrocannabinol" in Pubic Hair of Cannabis Abuser: Target Ion GC-MS Method (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
Cannabis substance abuse is widely causing addiction across the world. In the drug of abuse cases, hair plays an important role in identifying drug abuse and drug history consumption. However, scalp hair may not be available in every drug abuse cases; other body hairs play an essential role in forensic toxicological analysis. This study attempt has been made to use pubic hair as an alternative specimen for the detection of 11-Nor-9-carboxy-Δ9 - Tetrahydrocannabinol metabolite of cannabis abusers using the target ion by GC-MS method. Pubic hairs of 10 years cannabis abusers were collected and used for GC-MS analysis to detect THC-COOH metabolite. The study confirmed the presence of THC-COOH metabolite with the help of 371 target ions. This method will be useful in identifying the presence of cannabis in drug-facilitated crimes for forensic toxicological analysis. In further, this method would also be useful in identifying single drug exposure cases.
Keywords: Pubic hair; 11-Nor-9-carboxy-Δ9 -Tetrahydrocannabinol; Drug abuser; Target ion GC-MS; Forensic toxicology